Collaboratories: Improving Research Capabilities in Chemical and Biomedical Sciences: Proceedings of a Multi-site Electronic Workshop (The National Academies Press, 1999)

Global Ocean Science: Toward an Integrated Approach - National Research Council (The National Academies Press, 1999)
During recent years, large-scale investigations into global climate change and other highly visible issues have taken the lion's share of declining research funds. At the same time, funding for basic research in such core disciplines as physical oceanography, biological oceanography, chemical oceanography, and marine geology has dwindled. Global Ocean Science examines how the largest U.S. ocean research programs, such as the Ocean Drilling Program (ODP) and the Joint Global Ocean Flux Study (JGOFS), have significantly contributed to our understanding of the oceans. The book examines the impact of these programs on research, education, and collegiality within this diverse scientific community and offers recommendations to help ensure a vital future for ocean science, including: Specific results of the programs such as data collected, conceptual breakthroughs, information published, demonstrable use of program products, incorporation of new knowledge into education, and contribution to policymaking and decisionmaking by federal agencies. Mechanisms for efficiently identifying knowledge gaps and research questions, strategic planning of research programs, managing competitive proposals, securing needed resources, and more. This practical book will be welcomed by ocean investigators, users of oceanographic research findings, policymakers, administrators, educators, and students.

Making Climate Forecasts Matter - National Research Council (The National Academies Press, 1999)
El Nino has been with us for centuries, but now we can forcast it, and thus can prepare far in advance for the extreme climatic events it brings. The emerging ability to forecast climate may be of tremendous value to humanity if we learn how to use the information well. How does society cope with seasonal-to-interannual climatic variations? How have climate forecasts been used2014and how useful have they been? What kinds of forecast information are needed? Who is likely to benefit from forecasting skill? What are the benefits of better forecasting? This book reviews what we know about these and other questions and identifies research directions toward more useful seasonal-to-interannual climate forecasts. In approaching their recommendations, the panel explores: Vulnerability of human activities to climate. State of the science of climate forecasting. How societies coevolved with their climates and cope with variations in climate. How climate information should be disseminated to achieve the best response. How we can use forecasting to better manage the human consequences of climate change.

Global Environmental Change: Research Pathways for the Next Decade - National Research Council (The National Academies Press, 1999)
How can we understand and rise to the environmental challenges of global change? One clear answer is to understand the science of global change, not solely in terms of the processes that control changes in climate and the composition of the atmosphere, but in how ecosystems and human society interact with these changes. In the last two decades of the twentieth century, a number of such research efforts2014supported by computer and satellite technology2014have been launched. Yet many opportunities for integration remain unexploited, and many fundamental questions remain about the earth's capacity to support a growing human population. This volume encourages a renewed commitment to understanding global change and sets a direction for research in the decade ahead. Through case studies the book explores what can be learned from the lessons of the past 20 years and what are the outstanding scientific questions. Highlights include: Research imperatives and strategies for investigators in the areas of atmospheric chemistry, climate, ecosystem studies, and human dimensions of global change. The context of climate change, including lessons to be gleaned from paleoclimatology. Human responses to2014and forcing of2014projected global change. This book offers a comprehensive overview of global change research to date and provides a framework for answering urgent questions.

Adequacy of Climate Observing Systems - National Research Council (The National Academies Press, 1999)
The 1997 Conference on the World Climate Research Programme to the Third Conference of the Parties of the United Nations Framework Convention on Climate Change concluded that the global capacity to observe the Earth's climate system is inadequate and is deteriorating worldwide. As a result, the chair of the subcommittee of the U.S. Global Change Research Program (USGCRP) requested a National Research Council study to assess the current status of the climate observing capabilities of the United States. This report focuses on existing observing systems for detection and attribution of climate change, with special emphasis on those systems with long time series.

Biographical Memoirs: Volume 76 - National Academy of Sciences (The National Academies Press, 1999)
Biographic Memoirs: Volume 76 contains the biographies of deceased members of the National Academy of Sciences and bibliographies of their published works. Each biographical essay was written by a member of the Academy familiar with the professional career of the deceased. For historical and bibliographical purposes, these volumes are worth returning to time and again.

From Monsoons to Microbes: Understanding the Ocean's Role in Human Health - National Research Council
What can sharks teach us about our immune system? What can horseshoe crabs show us about eyesight? The more we learn about the ocean, the more we realize how critical these vast bodies of water are to our health and well-being. Sometimes the ocean helps us, as when a marine organism yields a new medical treatment. At other times, the ocean poses the threat of coastal storm surges or toxic algal blooms. From Monsoons to Microbes offers a deeper look into the oceans that surround us, often nurturing yet sometimes harming humankind. This book explores the links among physical oceanography, public health, epidemiology, marine biology, and medicine in understanding what the ocean has to offer. It will help readers grasp such important points as: How the ocean's sweeping physical processes create long-term phenomena such as El Nino and short-term disastrous events such as tsunamis2014including what communities can do to prepare. What medicines and nutritional products have come from the ocean and what the prospects are for more such discoveries. How estuaries work2014where salt and fresh water meet2014and what can go wrong, as in the 7,000 square mile \

Ensuring Quality Cancer Care - Institute of Medicine (The National Academies Press, 1999)
We all want to believe that when people get cancer, they will receive medical care of the highest quality. Even as new scientific breakthroughs are announced, though, many cancer patients may be getting the wrong care, too little care, or too much care, in the form of unnecessary procedures. How close is American medicine to the ideal of quality cancer care for every person with cancer? Ensuring Quality Cancer Care provides a comprehensive picture of how cancer care is delivered in our nation, from early detection to end-of-life issues. The National Cancer Policy Board defines quality care and recommends how to monitor, measure, and extend quality care to all people with cancer. Approaches to accountability in health care are reviewed. What keeps people from getting care? The book explains how lack of medical coverage, social and economic status, patient beliefs, physician decision-making, and other factors can stand between the patient and the best possible care. The board explores how cancer care is shaped by the current focus on evidence-based medicine, the widespread adoption of managed care, where services are provided, and who provides care. Specific shortfalls in the care of breast and prostate cancer are identified. A status report on health services research is included. Ensuring Quality Cancer Care offers wide-ranging data and information in clear context. As the baby boomers approach the years when most cancer occurs, this timely volume will be of special interest to health policy makers, public and private healthcare purchasers, medical professionals, patient advocates, researchers, and people with cancer.

A Vision for the National Weather Service: Road Map for the Future - National Research Council (The National Academies Press, 1999)
In this study, the committee explores ways the National Weather Service (NWS) can take advantage of continuing advances in science and technology to meet the challenges of the future. The predictions are focused on the target year 2025. Because specific predictions about the state of science and technology or the NWS more than 25 years in the future will not be entirely accurate, the goal of this report is to identify and highlight trends that are most likely to influence change. The Panel on the Road Map for the Future National Weather Service developed an optimistic vision for 2025 based on advances in science and technology.

Review of NASA's Distributed Active Archive Centers - National Research Council (The National Academies Press, 1999)

(NAS Colloquium) Plants and Population: Is There Time? (The National Academies Press, 1999)

Our Common Journey: A Transition Toward Sustainability - National Research Council
World human population is expected to reach upwards of 9 billion by 2050 and then level off over the next half-century. How can the transition to a stabilizing population also be a transition to sustainability? How can science and technology help to ensure that human needs are met while the planet's environment is nurtured and restored? Our Common Journey examines these momentous questions to draw strategic connections between scientific research, technological development, and societies' efforts to achieve environmentally sustainable improvements in human well being. The book argues that societies should approach sustainable development not as a destination but as an ongoing, adaptive learning process. Speaking to the next two generations, it proposes a strategy for using scientific and technical knowledge to better inform future action in the areas of fertility reduction, urban systems, agricultural production, energy and materials use, ecosystem restoration and biodiversity conservation, and suggests an approach for building a new research agenda for sustainability science. Our Common Journey documents large-scale historical currents of social and environmental change and reviews methods for \

Proceedings of the Workshop on Promoting Access to Scientific and Technical Data for the Public Interest: An Assessment of Policy Options (The National Academies Press, 1999)

Safety of Silicone Breast Implants - Institute of Medicine (The National Academies Press, 1999)
The Dow Corning case raised serious questions about the safety of silicone breast implants and about larger issues of medical device testing and patient education. Safety of Silicone Breast Implants presents a well-documented, thoughtful exploration of the safety of these devices, drawing conclusions from the available research base and suggesting further questions to be answered. This book also examines the sensitive issues surrounding women's decisions about implants. In reaching conclusions, the committee reviews: The history of the silicone breast implant and the development of its chemistry. The wide variety of U.S.-made implants and their regulation by the Food and Drug Administration. Frequency and consequences of local complications from implants. The evidence for and against links between implants and autoimmune disorders, connective tissue disease, neurological problems, silicone in breast milk, or a proposed new syndrome. Evidence that implants may be associated with lower frequencies of breast cancer. Safety of Silicone Breast Implants provides a comprehensive, well-organized review of the science behind one of the most significant medical controversies of our time.

(NAS Colloquium) The Neurobiology of Pain (The National Academies Press, 1999)